Analysis and applicability of the research in the strengthening of the quality standards of the Integral Professional Training of the Agroindustrial Training Center, Huila Regional - Saavedra Mora, David
The scientific research processes are the basis to build and generate knowledge from the solution of problems of the productive sector; being the theory, experimentation, generation and social appropriation of knowledge, the route to solve part of the inconveniences. This article presents the evolution in the implementation of the applied research process, carried out between 2014 and 2017. The methodology includes a documentary and descriptive analysis, in an overview of the results of the SENNOVA program lines.